Developing research skill in students of Socio-cultural Management for Development: experimental outcomes of an estrategy - Castillo Amaro, Mariano; Mena Campos, Alodio; Batista Salvador, Amaury (Transformación, 2024)
Objective: To assess the effectiveness of a pedagogical strategy, as a practical instrument for the researching skills development in students of the Sociocultural Management for Development major at the University of Camagüey.Methods: Theoretical and empirical research methods were used to achieve the stated objective, including documentary analysis, interviews, a checklist and the Liker scale. The study follows the structural-functional systemic approach.Result: It was possible to corroborate the feasibility of implementing a pedagogical strategy for the training of research skills in students of Sociocultural Management for Development based on the demands of the current curriculum.Conclusion: the study carried out is novel for Social Sciences majors, in particular for the training of research skills in students of the Sociocultural Management for Development major and has value for its practical implementation both for the systematized information and for its use. by teachers and students in the training process of research skills in Sociocultural Management for Development students, so that the participants may have a practical tool for their professional work at their disposal.
Keywords: training, skills; research; development